2016
DOI: 10.1080/14397595.2016.1259729
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of natural eggshell membrane (NEM) on multiple indices of arthritis in collagen-induced arthritic rats

Abstract: NEM significantly improved multiple aspects of inflammatory arthritis including inflammation, pannus, cartilage damage, bone resorption, and periosteal bone formation. This study provides further support for the use of CTXII, COMP, and A2M as relevant biomarkers that were responsive to NEM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 65 publications
(88 reference statements)
0
20
0
Order By: Relevance
“…IL-17 is a cytokine during the process that T lymphocytes promote and induce the inflammation, and it has functions of promoting immune response, inflammation development and hematopoiesis ( 17 ). Results of the current study showed that the levels of IL-17 in model observation group at 1, 7, 14, 21 and 28 days were significantly higher than those in blank control group (P<0.05), and the level was positively correlated with AI score and pedal swelling volume.…”
Section: Discussionmentioning
confidence: 99%
“…IL-17 is a cytokine during the process that T lymphocytes promote and induce the inflammation, and it has functions of promoting immune response, inflammation development and hematopoiesis ( 17 ). Results of the current study showed that the levels of IL-17 in model observation group at 1, 7, 14, 21 and 28 days were significantly higher than those in blank control group (P<0.05), and the level was positively correlated with AI score and pedal swelling volume.…”
Section: Discussionmentioning
confidence: 99%
“…A hydrolysate of NEM was found to activate NF-κB in vitro, 40 and in a subsequent study employing the CIA rat model, oral supplementation with NEM substantially suppressed swelling due to inflammation and markedly lessened cartilage damage, pannus formation, and periarticular bone resorption histologically. 31 Immune tolerance to cartilage components, particularly type II collagen, from oral supplementation with NEM (which contains types I, V, and X collagen) is a more likely explanation for the longer-term reduction in CTX-II formation demonstrated here than is direct suppression of localized inflammation in the joints experiencing strain from exercise.…”
Section: Discussionmentioning
confidence: 77%
“… 24 ESM is known to reduce the expression of various pro-inflammatory cytokines, including the key mediators of inflammation interleukin-1 beta (IL-1β) and tumor necrosis factor-alpha (TNF-α) both in vitro 25 and in vivo. 26 A proprietary form of ESM, commercially available as the branded product NEM ® (natural eggshell membrane); ESM Technologies, LLC, Carthage, MO, USA), has demonstrated safety and efficacy in multiple clinical trials in relieving joint pain and stiffness in humans with OA 27 29 and has been shown to reduce CTX-II levels in rat models of both OA 30 and RA 31 and in naturally occurring joint disease in dogs. 32 …”
Section: Introductionmentioning
confidence: 99%
“…ESM-P has been reported to have a skin-moisturising effect and to ameliorate knee joint pain [5, 6]. Similar effects have been reported for hyaluronic acid [19, 20].…”
Section: Discussionmentioning
confidence: 78%
“…Eggshell membranes have been used as carbon dioxide and heavy metal absorbers [2, 3], and also in sauces such as soy sauce [4]. They have also been reported to have a skin-moisturising effect and to ameliorate knee joint pain [5, 6]. To clarify these and other potential health functions, it is important to elucidate the action mechanisms of eggshell membrane protein (ESM-P).…”
Section: Introductionmentioning
confidence: 99%